Achievable or unbelievable? Expert perceptions of the European Union targets for emissions, renewables, and efficiency. (December 2017) - Khanam, Tahamina; Rahman, Abul; Mola-Yudego, Blas; Pelkonen, Paavo; Perez, Yannick; Pykäläinen, Jouni
Abstract: In 2007, the European Union (EU) set goals to reduce greenhouse gas (GHG) emissions, called H2020 targets, by 2020. Following the adoption and implementation of policies related to these targets, this study surveyed 187 experts from 25 EU countries to analyse their perceptions regarding the achievement of the H2020 targets. The experts' countries are grouped in five geographical regions: Central European countries (CEC), Western European countries (WEC), South-Eastern European countries (SEEC), Nordic countries (NC), and East European countries (EEC). The survey results demonstrate a broad scepticism among those interviewed: 49% perceive that the renewable energy (RE) target will not be accomplished, 60% perceive that the EU's GHG emission policies are not sufficient to fulfil the GHG reduction target, and 85% state that the EU's energy efficiency will not succeed. The regional comparison reveals that an overwhelming majority (82–93%) from SEEC, NC, and EEC feel that consistent and sufficient incentives are necessary to meet the RE targets for biomass. Contrary to the majority opinion among WEC experts, the majority from all other regions perceive that the EU GHG policies are insufficient and that the H2020 targets will not be achieved.